Revisiting the Role of Education in Social Transformation: Insights from Fianarantsoa, Madagascar - Michel, Rakotoniriana Noelisoa Jean; Sulla, Razafitahindraza Erica Feyzine; Esmati, Shahabuddin (MEDIA DAN STRATEGI PEMBELAJARAN, 2026)
This study aims to examine the role of education in social transformation within the context of Fianarantsoa in Madagascar, with particular attention to how access, quality, and learning outcomes influence individual and collective trajectories. Grounded in a socio-educational perspective, the research addresses the gap between the widespread expectation that education leads to social mobility and the observed realities of persistent inequality and limited employment opportunities. A qualitative research design was adopted, involving purposive sampling of 20 participants, including teachers, students, parents, school administrators, and community leaders. Data was collected through semi-structured interviews and supported by document analysis, then analyzed using a thematic approach to identify key patterns related to educational experiences and social impact. The findings indicate that education is highly valued as a pathway to improved living conditions and social recognition, reflecting its strong symbolic importance within society. However, disparities between urban and rural areas in terms of infrastructure, resources, and teaching quality contribute to uneven learning outcomes. Many students complete schooling without mastering essential literacy, numeracy, and practical skills, which limits their ability to access meaningful employment. The results suggest that education functions as a necessary but insufficient condition for social mobility, as broader socio-economic and institutional constraints shape its impact. The study highlights the need to improve the quality and relevance of education, strengthen teachers’ capacity, and address structural inequalities to enhance education’s contribution to sustainable development and social transformation